The genus Caenocrepis Thomson (Hymenoptera: Pteromalidae) in the Afrotropical region, with a key to world species - Mitroiu, Mircea-Dan (Zootaxa, 2012)
Caenocrepis Thomson (Hymenoptera: Pteromalidae) is recorded for the first time in the Afrotropical region and two species, C. simonae sp. nov. and C. formidolosa sp. nov., are newly described from Mozambique and Zimbabwe. A key to the world species of the genus is provided. The two new species show some interesting morphological features such as enlarged clypeal lobes and unusually wide temples, which are not present in any Palaearctic species.